Observasi Penerapan Sanitasi dan Higiene Karyawan pada Produksi Susu Pasteurisasi di UMKM X di Kota XX - Dyah Ayu Pradnya Paramitha; Muhammad Mar'ie Sirajuddin (Pengelola Jurnal Politeknik Negeri Ketapang, 2023)
Sanitation and hygiene are one of the important requirements in maintaining food quality and safety in order to produce a product that is safe, healthy and clean. Therefore, to maintain the quality and safety of pasteurized milk products, it is necessary to observe the implementation of employee sanitation and hygiene in the processing of pasteurized milk products at MSME X. The data collection method used to analyze the problem is using data collection techniques using observation, interviews, and literature studies. The problem solving methodology uses the 2012 CPPB-IRT and fishbone diagrams. The results of the analysis show that the application of the principles of sanitation and hygiene for pasteurized milk production employees at MSME X is quite good. Then, after further observation, it was concluded that the things of particular concern were the work clothes and environmental maintenance. For the sanitation of buildings and facilities, the matter of concern is in terms of waste and also building construction such as floors, walls and ventilation. In terms of equipment sanitation, attention is paid to the order in which production equipment is placed. Therefore, it is necessary to improve and implement better sanitation and hygiene for employees of the pasteurized milk production process at MSME X.